Treatment Outcomes of Well‐Differentiated High‐Grade Neuroendocrine Tumors. (8th February 2021) - Liu, Alex J.; Ueberroth, Benjamin E.; McGarrah, Patrick W.; Buckner Petty, Skye A.; Kendi, Ayse Tuba; Starr, Jason; Hobday, Timothy J.; Halfdanarson, Thorvardur R.; Sonbol, Mohamad Bassam
Abstract: Introduction: Recent classification of neuroendocrine neoplasms has defined well‐differentiated high‐grade neuroendocrine tumors (NET G3) as a distinct entity from poorly differentiated neuroendocrine carcinoma. The optimal treatment for NET G3 has not been well‐described. This study aimed to evaluate metastatic NET G3 response to different treatment regimens. Materials and Methods: This was a retrospective study of patients with NET G3 within the Mayo Clinic database. Patients' demographics along with treatment characteristics, responses, and survival were assessed. Primary endpoints were progression‐free survival (PFS) and overall survival. Secondary endpoints were objective response rate (ORR) and disease control rate (DCR). Results: Treatment data was available in 30 patients with median age of 59.5 years at diagnosis. The primary tumor was mostly pancreatic (73.3%). Ki‐67 index was ≥55% in 26.7% of cases. Treatments included capecitabine + temozolomide (CAPTEM) ( n = 20), lutetium 177 DOTATATE (PRRT; n = 10), Platinum‐etoposide (EP; n = 8), FOLFOX ( n = 7), and everolimus ( n = 2). CAPTEM exhibited ORR 35%, DCR 65%, and median PFS 9.4 months (95% confidence interval, 2.96–16.07). Both EP and FOLFOX showed similar radiographic response rates with ORR 25.0% and 28.6%; however, median PFS durations were quite distinct at 2.94 and 13.04 months, respectively. PRRT had ORR of 20%, DCR of 70%, and median PFS of 9.13 months. Conclusion: Among patients with NET G3, CAPTEM was the most commonly used treatment with clinically meaningful efficacy and disease control. FOLFOX or PRRT are other potentially active treatment options. EP has some activity in NET G3, but responses appear to be short‐lived. Prospective studies evaluating different treatments effects in patients with NET G3 are needed to determine an optimal treatment strategy. Implications for Practice: High‐grade well‐differentiated neuroendocrine tumors (NET G3) are considered a different entity from low‐grade NET and neuroendocrine carcinoma in terms of prognosis and management. The oral combination of capecitabine and temozolomide is considered a good option in the management of metastatic NET G3 and may be preferred. FOLFOX is another systemic option with reasonable efficacy. Similar to other well‐differentiated neuroendocrine tumors, peptide receptor radionuclide therapy seems to have some efficacy in these tumors. Abstract : This article evaluates the clinical outcomes of patients with well‐differentiated high‐grade neuroendocrine tumors treated with different cytotoxic regimens at Mayo Clinic.